AQUATIC TOXICITY BIOASSAY OF CASSAVA MILL EFFLUENT USING TADPOLES (SCLEROPHRYS REGULARIS) - Agbeyi, Erhomarhua Victor; Odia, Mamuyovwi; Onadje, Festus Ovwighose (FUDMA JOURNAL OF SCIENCES, 2025)
During the production of garri, starch and tapioca from cassava, cassava effluents are usually produced as by-product and this by-product contains cyanide and other substances. This study was intended to investigate a 96-hour toxicity test of cassava effluent on tadpoles to check the aquatic environmental health status. Two hundred and ten (210) tadpoles with length and weight ranging from 2.8 -3.5 cm and 0.24 -0.47 mg respectively were collected from a puddle, 150 - 200m from the cassava mill shed and were randomly divided in tens and in duplicate into group A,B,C,D,E and F. Group A is the control. Group B, C, D, E and F were treated with 5ml/L, 10ml/L, 15ml/L, 20ml/L and 25ml/L of the cassava mill effluent with an LC50 of 7.6ml/L. Result showed that there was no death in 5ml/L group B in the 96 hours toxicity test compared with the control. However, in the 10ml/L group C there was a total death of 8 tadpoles in 24, 48, 72 and 96hours of exposure compared with the control. In 15ml/L, 20ml/L and 25ml/L doses there was no survival throughout the period of the experiment p<0.05. This study indicated that untreated cassava mill effluent should not be discharge into water body without treatment to save the aquatic lives in the water body.